Changes in force and velocity during the sprint start with different front & rear block angles - Cousins, S.; Fiolkowski, P.; Ford, P. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: One of the factors influencing the sprint start is the ability of the athlete to attain a high force generation out of the starting blocks, therefore to increase start velocity an athlete must improve their power output during the start (Baumann, 1976); however very few studies have considered how these variables are affected by altering front and rear starting block angle. The aim of this study to evaluate the influence of different combinations of front (FBA) and rear block angels (RBA) upon force generation at each block, and to consider the forces in relation to the sprinting speed in the initial phase of the race. Methods Twelve male club-level track sprinters performed a start using different combinations of front (300, 400 and 500) and rear (300, 400 and 500) block angles. The order of testing was randomised and the spacing between the blocks constant for each subject. Two force platforms (Kistler, UK) were situated within a specially designed outdoor polyflex surface (IAAF standard); the platforms were lowered into the surface and covered with a polyflex layer. Cantabrian starting blocks for both feet were mounted separately onto the polyflex surface. These blocks allowed the front and rear block angle to be varied independently with 100 intervals. Cla-win (University College Chichester) infrared timing gates were placed immediately parallel to the starting blocks and at 5 metre intervals to determine sprint speed over the first 5 and 10 metres. Force data were analysed to determine mean peak horizontal (Fx) and vertical (Fy) force levels occurring during the start at both the front and rear foot. An ANOVA with repeated measures was performed to examine significant differences in force production and sprint speed with the different combination of block angles. Results The greatest overall mean force for both blocks occurred for the 300 FBA in combination with the 300 RBA, followed by the 400 FBA and the 300 RBA (Figure 1). Relatively the 300 RBA gave the greatest Fx and Fy forces regardless of which FBA were used. Significantly higher Fx, Fy, resultant and overall forces were achieved with the 300 FBA compared to the 400 and 500 block angles (p<0.05). Mean speeds were significantly higher with the 300 FBA over 5 and 10m (p<0.05); performance with the 300 FBA was also much faster in combination with a RBA of 300. A Pearson correlation of 0.833 (p<0.05) and 0.733 (p<0.05) revealed a relationship between front block resultant forces and velocity at both 5 and 10m respectively.